2021
DOI: 10.1021/acsomega.1c03586
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production from Waste Cooking Oil Catalyzed by a Bifunctional Catalyst

Abstract: The objective of this study was to prepare bifunctional catalysts based on iron and CaO and test them in the biodiesel production using waste cooking oil (WCO) as feedstock. Two iron precursors were studied, Fe2O3 and Fe­(NO3)3·9H2O. The identified crystalline phases were Ca2Fe2O5 and CaFeO3. Surface morphology and textural properties (distribution of active species, specific surface area, size, and pore volume) were also analyzed. Additionally, thermal stability was studied and 800 °C was established as the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 55 publications
1
5
0
3
Order By: Relevance
“…This shows that the adsorbent is crystalline in nature. The nding of this study is in agreement with previous studies, 53,55 thereby corroborating the results obtained in the SEM-EDX and FTIR analysis.…”
Section: Surface Chemistry Of the Biosorbentsupporting
confidence: 93%
“…This shows that the adsorbent is crystalline in nature. The nding of this study is in agreement with previous studies, 53,55 thereby corroborating the results obtained in the SEM-EDX and FTIR analysis.…”
Section: Surface Chemistry Of the Biosorbentsupporting
confidence: 93%
“…308 Metals and their oxides can be mixed to provide bifunctional catalysts that can perform the acid-catalyzed esterification of FFA and base-catalyzed transesterification of triglycerides in a single step, reducing the reaction time and cost on a commercial scale. 309 The majority of current research focuses on enhancing stability or regeneration methods such as solvent washing or recalcination. Lee et al have reported the catalytic activity of various mixed metal oxides, like CaO–MgO, CaO–ZnO, CaO–La 2 O 3 , and MgO–ZnO, with Jatropha oil, and found that their activity as compared to their oxides enhanced in the order CaO–ZnO > CaO ∼ CaO–MgO ∼ CaO–La 2 O 3 > MgO–ZnO > MgO > ZnO > La 2 O 3 .…”
Section: The Relevance Of Catalysis To Biodiesel Productionmentioning
confidence: 99%
“…Reaksi trans-esterifikasi memerlukan katalis untuk mendapatkan rendemen biodiesel yang lebih banyak dan lebih berkualitas. Katalis basa heterogen lebih baik digunakan dalam proses reaksi trans-esterifikasi biodiesel dibandingkan dengan katalis basa homogen, karena dapat menghasilkan rendemen proses trans-esterifikasi lebih tinggi (Elliyanti et al, 2017) dan (Enguilo Gonzaga et al, 2021). Pada penelitian ini digunakan katalis basa heterogen yaitu katalis CaO dari limbah cangkang telur ayam broiler.…”
Section: Proses Trans-esterifikasiunclassified
“…Penelitian (Oko & Feri, 2019) menghasilkan rendemen 96,073% dari minyak jarak. Hal tersebut dapat terjadi karena proses reaksi transesterifikasi dipengaruhi oleh beberapa faktor, yaitu kandungan asam lemak bebas dan kelembaban minyak, katalis, perbandingan molar alkohol dengan minyak, suhu reaksi dan waktu reaksi (Enguilo Gonzaga et al, 2021;Erchamo et al, 2021).…”
Section: Proses Trans-esterifikasiunclassified